The power of technology in CRE data and analytics - GOH, Clarence (Institutional Knowledge at Singapore Management University, 2015)
Many companies are using data to drive competitiveadvantage. Across industries, there is rapidly growingappreciation that data-driven insights can substantiallyimprove decision making across a wide range of businessfunctions, and corporate real estate (CRE) is no exception.